CHILD BRITISH FOLK BALLAD: TYPIFICATION OF AN IMAGE-CHARACTER - Карбашевська, О. В. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article examines into the problem of typifying a folk image-character in the British folk ballad on the material of the Scottish ballad «The traditional Gay Goshawk» (Child № 96, 7 versions), makes parallels with Ukrainian folklore, namely the historical ballad «Iz-za hory, hory, z temnenkoho lisu» («From beyond the Mountain, Mountain, from the Dark Forest», according to O. Dei’s classification III−A-11), proves commonality of the oral-poetic traditions in employment of tropes to create generalized pictures-portraits of heroines.